Treatment of Retained Fetal Membranes in the Mare—A Practitioner Survey - Warnakulasooriya, Dinuka N.; Marth, Christina D.; McLeod, Jacqueline A.; Hanlon, David W.; Krekeler, Natali (Frontiers in Veterinary Science, 2018)
Retained fetal membranes (RFM) is a common postpartum problem in mares for which the treatment is highly variable. The aim of this study was i) to investigate the different treatments used by equine practitioner for RFM and ii) to determine if there is a difference between treatments used by reproductive specialists and general equine practitioners. Information regarding treatment of RFM was sought from veterinary practitioners via a survey and this was compared to recommendations in the current literature. The survey was sent out to equine veterinarians and mixed practitioners with a high equine case load. Most treatments of RFM were in line with current recommendations, while some obsolete practices are still routinely performed by a small number of practitioners. Treatment recommendations for RFM have changed over the last few decades, but there are no universally accepted guidelines. The vast variety of treatments reported by practitioners in the present survey reflect this lack of guidance. More extensive research is needed in this area to establish evidence-based, uniformly agreed upon protocols.